2015
DOI: 10.1590/1677-3225v14n3a07
|View full text |Cite
|
Sign up to set email alerts
|

Morse taper internal connection implants: would abutment reseating influence retention?

Abstract: Aim: To investigate whether the removal and reseating of the abutment influences the retention of Morse taper implant system. Methods: Two Morse taper implant systems were selected: Bicon Dental Implant TM system (Bicon, LLC, Boston, MA, USA) and Kopp Implant ® system (Kopp ® , Curitiba, PR, Brazil). In both systems, the abutment is connected to the implant with a locking taper. To seat the abutment, the same vertical force was applied in both systems. It was measured the compressive force necessary to engage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…As a result, the first null hypothesis was rejected. After compressive loading, Rabelo et al 18 measured the tensile force of two Morse taper implant systems (the Kopp and Bicon systems). It was observed that higher compressive forces generated higher tensile strengths in both implant systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the first null hypothesis was rejected. After compressive loading, Rabelo et al 18 measured the tensile force of two Morse taper implant systems (the Kopp and Bicon systems). It was observed that higher compressive forces generated higher tensile strengths in both implant systems.…”
Section: Discussionmentioning
confidence: 99%
“…18 Therefore, a positive correlation between compressive loading and removal forces was observed. 18 There is no data in the current dental literature on the long-term effects of chewing forces on the retention and stability of an indexed conometric system (Acuris conometric system) between indexed cap-abutment. As a result, the purpose of this in vitro study was to evaluate the retention force of this conometric system following thermomechanical aging in a chewing simulator.…”
mentioning
confidence: 89%
“…Kopp friction system consists of a cylindrical abutment with less than 2° between the inner walls of the implant and the outer walls of the abutment, which when coupled to the implant requires a removal force greater than the insertion force (Steiner et al, 2009;Ricciardi Coppedê et al, 2009;Rabelo et al). This Morse taper interface is related to the phenomenon of cold welding, which occurs through the intimate contact between the surfaces of the prosthetic abutment and the implant, leading to an interlock between the parts and, consequently, greater friction retention and stability (Steiner et al).…”
Section: Discussionmentioning
confidence: 99%
“…The FMTI has some advantages, such as the possibility of adequate aesthetics in the cervical region and a lower number of prosthetic components, with consequent reduction of costs, ease in clinical procedures, and increased resistance to fracture of the prosthetic abutment (Rabelo et al, 2015). Stability of the abutment is fundamental to achieve aesthetics and longevity of the prostheses, which is fundamental to the success of and satisfaction with the rehabilitation (Rack et al;Aguirrebeitia et al, 2014;Rabelo et al). Although this system promotes interlock between the components, the professional may need to remove the abutment for some reason.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation